Theoretical model of business transformation with a focus on strategic resources: Towards competitive improvement - Arias Hancco, Jeymi Fabiola (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Companies are an essential part of the global economic system, and contribute significantly to its sustained growth, promoting development through the generation of employment and wealth creation. In this sense, the objective of this research was to design a theoretical model of business transformation with a focus on strategic resources, leading to competitive improvement. The research encompasses a pure level study, including a descriptive, explanatory and relational design; aimed at 127 companies in the agro-export sector of the Tacna Region, Peru. The proposed theoretical model breaks down different dimensions that explain competitiveness in its various phases.